The Pharmacology of Cannabinoids in Chronic Pain - Alonso Cortez-Resendiz; Timothy J. Leiter; Steven M. Riela; Nicholas M. Graziane; Wesley M. Raup-Konsavage; Kent E. Vrana (Medical Cannabis and Cannabinoids)
Background: Our objective was to provide an overview of the currently available scientific and clinical data supporting the use of Cannabis and Cannabis-derived products for the treatment of chronic pain disorders. We also provide information for researchers, clinicians, and patients to be better informed and understand the approach behind the recommendation of Cannabis as a potential adjuvant in the treatment/control of chronic pain. Cannabis and its bioactive compounds have sparked interest in the field of pain treatment in spite of its controversial history and status as a controlled substance in many countries. With the increase in chronic pain, physicians and patients have started to look at alternative ways to treat pain aside from traditional treatments. One alternative is the use of cannabis to reduce/treat chronic pain disorders based on anecdotal accounts and the function of its phytocannabinoids. The two main cannabinoids in cannabis, tetrahydrocannabinol (THC) and cannabidiol, act on CB1 and CB2 receptors (in addition to several additional receptors). It is through these pleiotropic receptor interactions that these compounds elicit their biological function including the reduction of chronic pain. In this narrative review, we included the most recent evidence supporting the use of cannabis in the treatment of chronic pain disorders including chronic neuropathic pain, cancer-induced neuropathic pain, chronic musculoskeletal pain, and chronic headaches and migraines. Summary: Evidence suggests that cannabis and cannabinoids have an analgesic effect that arises from a combination of compounds and various receptor systems. These effects may be maximized with the use of a combination of cannabinoids. At the same time, the combination of cannabinoids helps minimize the undesirable side effects of some cannabinoids such as the psychoactivity of THC. With these findings, further research is necessary to assess the analgesic properties of other cannabinoids like cannabichromene and cannabigerol and their contributions to the reduction of pain. Key Messages: Cannabis and its bioactive compounds show potential in the reduction of chronic pain. Background: Our objective was to provide an overview of the currently available scientific and clinical data supporting the use of Cannabis and Cannabis-derived products for the treatment of chronic pain disorders. We also provide information for researchers, clinicians, and patients to be better informed and understand the approach behind the recommendation of Cannabis as a potential adjuvant in the treatment/control of chronic pain. Cannabis and its bioactive compounds have sparked interest in the field of pain treatment in spite of its controversial history and status as a controlled substance in many countries. With the increase in chronic pain, physicians and patients have started to look at alternative ways to treat pain aside from traditional treatments. One alternative is the use of cannabis to reduce/treat chronic pain disorders based on anecdotal accounts and the function of its phytocannabinoids. The two main cannabinoids in cannabis, tetrahydrocannabinol (THC) and cannabidiol, act on CB1 and CB2 receptors (in addition to several additional receptors). It is through these pleiotropic receptor interactions that these compounds elicit their biological function including the reduction of chronic pain. In this narrative review, we included the most recent evidence supporting the use of cannabis in the treatment of chronic pain disorders including chronic neuropathic pain, cancer-induced neuropathic pain, chronic musculoskeletal pain, and chronic headaches and migraines. Summary: Evidence suggests that cannabis and cannabinoids have an analgesic effect that arises from a combination of compounds and various receptor systems. These effects may be maximized with the use of a combination of cannabinoids. At the same time, the combination of cannabinoids helps minimize the undesirable side effects of some cannabinoids such as the psychoactivity of THC. With these findings, further research is necessary to assess the analgesic properties of other cannabinoids like cannabichromene and cannabigerol and their contributions to the reduction of pain. Key Messages: Cannabis and its bioactive compounds show potential in the reduction of chronic pain.